Pengaruh Pasar Modal Syariah dan Makroekonomi Terhadap Pertumbuhan Ekonomi Indonesia Periode 2014-2023 Menggunakan Vector Error Correction Model (VECM) - Suhendra Widi Prayoga; Afied Akhmad; Faris Iqbal Maulana Susanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Indonesia with its predominantly Muslim population, has great potential in developing the Islamic capital market to support the country's economy. This is indicated by the development of Islamic capital market instruments every year. In addition, macroeconomic aspects also affect the stability of the economy in a country. Therefore, this study was conducted to examine the influence between the Islamic capital market and macroeconomics on economic growth in Indonesia in the period 2014–2023. The data used are secondary data from various sources regarding the Islamic capital market, macroeconomics, and national economic growth. This research utilizes quantitative methods with descriptive analysis in the form of line diagrams and inference in the form of Vector Error Correction Model. The results showed that Islamic stocks have a causal relationship with economic growth. In the short-term model, Islamic capital market and macroeconomic variables have no significant influence on economic growth. However, Islamic stocks, Islamic bonds, Islamic mutual funds, exchange rates, and exports have a significant positive effect on economic growth in the long-term model. Meanwhile, inflation and imports have no significant effect on economic growth. The VECM model estimation results produced an R-Squared value of 79.63%.